Empoderando pais para a luta pelos direitos de seus filhos com deficiência: pesquisa-ação emancipatória - Araújo, Rosângela Martins de (2011)
Currently the perspective focused only on the individual and his or her disability has been replaced by researches on family-centered approaches and integrated with partnership and collaboration support process. This trend encouraged the creation of new parenting programs emphasizing family as a unit, including programs designed to empower parents of individuals with disabilities. Empower parents meant moving away from the notion of parents being compliant and passive recipients that allows them the opportunity to discuss and deal with their problems and possible solutions, and moreover professionals can also give confidence and enable parents to be actively engaged in the process of social transformation. Which strategies should be used to achieve this goal? To describe this issue, the purpose of the present paper was to develop and evaluate an intervention program endeavoring to develop the skills of parents of children with disabilities with regard to the human rights awareness to apply and defend them. We adopted the method of action research due to its capability to employ a collective and emancipator character, and interacting with the perspective of empowerment for the development in citizenship in accordance with the aim of this study. It was attended by 26 family members of people with severe and / or multiple disabilities. Measures to estimate the degree of parent empowerment, before and after the intervention, were collected using a scale. The intervention was performed in 11 meetings, taking into account that all meetings were video recorded and recorded in field diaries. Results indicated that intervention was appropriate to empower the participating parents regarding their rights; whereas they showed statistically significant results between pre- and post-intervention for 23 out of 26 parents within total score and / or in system advocacy, knowledge, and competence subscales. The qualitative data corroborated the quantitative findings and demonstrated that the impact of intervention seems to be beyond empowerment as well as served to build up social network of mutual support for family members. The measure of social validity of intervention indicated the average of 92% in parents approval, enhancing the quality indicators in the process of group intervention for family members. The study has shown that it is possible and beneficial to empower parents, and likewise it discusses the importance of researches to evaluate the impact of the intervention on parents of children with severe and multiple disabilities.